Uncertain time-dependent reliability analysis of corroded RC structures applying three-term conjugate method. (September 2020) - Bagheri, Mansour; Hosseini, Seyed Abbas; Keshtegar, Behrooz; Correia, José A.F.O.; Trung, Nguyen-Thoi
Highlights: The epistemic uncertainty is considered for time-dependent fuzzy reliability analysis of corroded RC beam. Fuzzy time-dependent reliability index is obtained using α -cut approach. The optimization method of hybrid HGAPSO is proposed to search the bounds of reliability index. Three-term conjugate method is used for computing the reliability index of RC beams under corrosion. Abstract: Evaluation of reinforced concrete (RC) structures which are subjected to the damaging environmental factors during the service life is critical. The service life model, the effects of environmental factors with their extent of damage during the service period of the structure could be predicted. Various uncertainties that came with this assessment confidence in the results should be taken by a safe margin. Structural reliability methods are one of the best tools to calculate the life model that considers the random properties of parameters. However, if the epistemic and inherent uncertainty of parameters with their time-dependent changes considered, the life model is more reliable. The reinforcement corrosion is the most damaging mechanism that causes the premature degradation of RC structures and substantial economic losses each year. In this work, the time-dependent reliability of an RC beam with chloride-induced corrosion considering epistemic uncertainty via an efficient numerical procedure is developed. Fuzzy time-dependent reliability index has been calculated using α -cut approach based on a hybrid version of genetic algorithm (GA) and particle swarm optimization (PSO), namely HGAPSO applying three-term conjugate reliability method. Results showed that the proposed numerical approach could efficiently and robustly estimate the fuzzy time-dependent reliability index.